2017
DOI: 10.14202/vetworld.2017.1227-1232
|View full text |Cite
|
Sign up to set email alerts
|

Clinicopathological alterations in naturally occurring Babesia gibsoni infection in dogs of Middle-South Gujarat, India

Abstract: Aim:The present research work was undertaken to describe various clinical signs and hematobiochemical alterations in dogs affected with Babesia gibsoni.Materials and Methods:Blood smears from a total of 79 suspected dogs of Anand region as well as Surat region of Gujarat state (India) were screened for detection of intraerythrocytic piroplasm of small form of Babesia. Diagnosis was made on the basis of clinical signs and demonstration of B. gibsoni organism in Giemsa-stained thin blood smears. The clinical sig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
16
0
3

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(26 citation statements)
references
References 24 publications
7
16
0
3
Order By: Relevance
“…Decreased TPP level of the present study was in agreement with report of (Helens, 2008;Turkar et al, 2009;Sharma et al, 2010;Sarma et al, 2011;Gaudarrama-Olhovich et al, 2013;Khatat et al, 2015 andBilwal et al, 2017). Hypoproteinaemia due to hypoalbuminaemia was caused by decreased intake and chronic inflammation (Gaudarrama-Olhovich et al, 2013).…”
Section: Blood Biochemical Profilesupporting
confidence: 92%
See 2 more Smart Citations
“…Decreased TPP level of the present study was in agreement with report of (Helens, 2008;Turkar et al, 2009;Sharma et al, 2010;Sarma et al, 2011;Gaudarrama-Olhovich et al, 2013;Khatat et al, 2015 andBilwal et al, 2017). Hypoproteinaemia due to hypoalbuminaemia was caused by decreased intake and chronic inflammation (Gaudarrama-Olhovich et al, 2013).…”
Section: Blood Biochemical Profilesupporting
confidence: 92%
“…Levels of AST and ALT increased significantly in dogs with anemia than healthy dogs. These findings were in accordance with (Castro et al, 2004;Helens, 2008;Sharma et al, 2010;Gaudarrama-Olhovich et al, 2013;Ghodasara et al, 2014;Bilwal et al, 2017 andBilwal et al, 2018) whereas, (Turkar et al, 2009) reported normal level of AST in anaemic dogs. Increased ALT and AST may be attributed to the hemolysis and cellular damage to the hepatic cells (Shrivastava et al, 2014).…”
Section: Blood Biochemical Profilesupporting
confidence: 80%
See 1 more Smart Citation
“…Hyperbilirubinemia was previously reported in camels infected with A. marginale due to excessive destruction of RBCs and the indirect hepatocellular damage [ 20 ]. Furthermore, elevated levels of T. Bil were shown to reflect intravascular and extravascular hemolysis [ 29 ]. Our results are also consistent with other investigations [ 26 , 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…En Asia, la especie predominante es B. gibsoni aunque B. vogeli se encuentra descripta en varios países asiáticos como la India (Singla et al, 2016), Turquía (Gülanber et al, 2006), Filipinas (Ybañez et al, 2017), Japón (Inokuma et al, 2004), China (Xu et al, incipiente respuesta inflamatoria ante la infección. El otro hallazgo fue la linfopenia que se presentó en el 70% de los casos, cuya interpretación -al menos en una parte de ellos-, podría explicarse por las infecciones virales y otras afecciones concurrentes a la piroplasmosis (Bilwal et al, 2017), aunque en muchos casos esta observación podría carecer de importancia clínica (comunicación personal, Eiras, 2018). En concordancia con la escasa patogenicidad reportada para B. vogeli (Jefferies, 2006;Solano-Gallego et al, 2016), en este trabajo la mayoría de los perros infectados se presentaron con muy baja parasitemia (1% o menos de los eritrocitos parasitados).…”
Section: -Discusión Y Conclusionesunclassified